2014
DOI: 10.1080/15481603.2014.972865
|View full text |Cite
|
Sign up to set email alerts
|

Remote-sensing perspective and GPR subsurface perception on the growth of a recently emerged spit at Talashil coast, west coast of India

Abstract: The growth as well as the internal structure of the recently emerged Talashil spit along the west coast of India was studied using multidate satellite images coupled with ground-penetrating radar (GPR) information. Decadal changes (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) in configuration, geomorphology and erosion and accretion pockets along the spit were traced and compared. A 170 m long subsurface profile across the spit from shoreline to river shore was generated using GPR. Histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, ground penetrating radar (GPR), a non-destructive technique, can be used to collect both point as well as spatial distribution of snow thickness. It has been widely used in ground mode, for snow and ice thickness measurements [8][9][10][11][12][13][14][15] , snowpack stratigraphic delineation 16 and to study the subsurface properties of other strata 17 . Forte et al 18,19 reported the applications of GPR data in determining the density and electromagnetic (EM) wave velocity for snow, firn and ice.…”
mentioning
confidence: 99%
“…However, ground penetrating radar (GPR), a non-destructive technique, can be used to collect both point as well as spatial distribution of snow thickness. It has been widely used in ground mode, for snow and ice thickness measurements [8][9][10][11][12][13][14][15] , snowpack stratigraphic delineation 16 and to study the subsurface properties of other strata 17 . Forte et al 18,19 reported the applications of GPR data in determining the density and electromagnetic (EM) wave velocity for snow, firn and ice.…”
mentioning
confidence: 99%